Autosomal Recessive Cerebellar Atrophy and Spastic Ataxia in Patients With Pathogenic Biallelic Variants in GEMIN5 - Rajan, Deepa S.; Kour, Sukhleen; Fortuna, Tyler R.; Cousin, Margot A.; Barnett, Sarah S.; Niu, Zhiyv; Babovic-Vuksanovic, Dusica; Klee, Eric W.; Kirmse, Brian; Innes, Micheil; Rydning, Siri Lynne; Selmer, Kaja K.; et al. (Frontiers in Cell and Developmental Biology, 2022)
The hereditary ataxias are a heterogenous group of disorders with an increasing number of causative genes being described. Due to the clinical and genetic heterogeneity seen in these conditions, the majority of such individuals endure a diagnostic odyssey or remain undiagnosed. Defining the molecular etiology can bring insights into the responsible molecular pathways and eventually the identification of therapeutic targets. Here, we describe the identification of biallelic variants in the GEMIN5 gene among seven unrelated families with nine affected individuals presenting with spastic ataxia and cerebellar atrophy. GEMIN5, an RNA-binding protein, has been shown to regulate transcription and translation machinery. GEMIN5 is a component of small nuclear ribonucleoprotein (snRNP) complexes and helps in the assembly of the spliceosome complexes. We found that biallelic GEMIN5 variants cause structural abnormalities in the encoded protein and reduce expression of snRNP complex proteins in patient cells compared with unaffected controls. Finally, knocking out endogenous Gemin5 in mice caused early embryonic lethality, suggesting that Gemin5 expression is crucial for normal development. Our work further expands on the phenotypic spectrum associated with GEMIN5-related disease and implicates the role of GEMIN5 among patients with spastic ataxia, cerebellar atrophy, and motor predominant developmental delay.